Phonetic-phonological and Lexical comparison of Lubuk Basung Sub-dialect with the Standard Minangkabaunese - Suksio, Adrian; Jufrizal, Jufrizal (Universitas Negeri Padang, 2024)
Suksio, Adrian.2024. Phonetic-phonological and Lexical Comparison Between the Standard Minangkabau With Lubuk Basung Sub-dialect. Article. Padang. Department of English Language and Literature. The Faculty of Language and Arts. Universitas Negeri Padang. The study aims to determine the differences between the Lubuk Basung sub-dialect located in Agam district, West Sumatera and the Minangkabau language as a standard dialect in West Sumatera province. In this study, find many things that will enrich our knowledge in the fields of grammar and linguistics and their relationship with dialectology.This research uses descriptive qualitative method. In this case, it is possible to compare two languages so that the differences, similarities, and uniqueness are found and to know how close the relationship between the languages is to be studied. Studies were conducted directly in Lubuk Basung, Agam District, West Sumatra Province, and then compared to Minangkabau as the standard language of West Sumatra, which was studied in Belimbing District, Padang City, West Sumatra Province.Lubuk Basung sub-dialect which is located in Lubuk Basung in Agam District of West Sumatra Province, do not recognize phoneme /r/ and phoneme /a/ in the end of the word is omitted and the phoneme /a/ change into phonem /u/ at the end of the word. KEYWORDS : PHONETIC-PHONOLOGICAL, LEXICAL , SUBDIAECT OF MINANGKABAU LANGUAGE